2014
DOI: 10.1007/s10152-014-0400-9
|View full text |Cite
|
Sign up to set email alerts
|

Relative growth and reproductive cycle of the date mussel Lithophaga lithophaga (Linnaeus, 1758) sampled from the Bizerte Bay (Northern Tunisia)

Abstract: Relative growth and the reproductive cycle of the date mussel Lithophaga lithophaga were studied from September 2002 to October 2003 in the Bizerte Bay (Northern Tunisia). Relationships between shell length and shell width, shell height as well as volume-related variables (shell dry weight, soft tissues dry weight and total wet weight) showed negative allometries in both sexes except for shell width in males (isometry) and shell height in both sexes (positive allometry). The sex ratio was unbalanced, within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Lithophaga lithophaga reproduces once a year following a decline in sea water temperature and has an unequal sex ratio, with males being dominant at smaller size categories (Galinou-Mitsoudi and Sinis 1994; Jaafar Kefi et al 2014). Growth and longevity of L. lithophaga have been studied by Kleeman (1973a, b) and Valli et al (1986) in the north Adriatic and Sinis (1994, 1995) in the Aegean Sea and according to the latter its longevity was estimated at >50 years.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lithophaga lithophaga reproduces once a year following a decline in sea water temperature and has an unequal sex ratio, with males being dominant at smaller size categories (Galinou-Mitsoudi and Sinis 1994; Jaafar Kefi et al 2014). Growth and longevity of L. lithophaga have been studied by Kleeman (1973a, b) and Valli et al (1986) in the north Adriatic and Sinis (1994, 1995) in the Aegean Sea and according to the latter its longevity was estimated at >50 years.…”
Section: Introductionmentioning
confidence: 98%
“…Most of the studies conducted on L. lithophaga addressed the anthropogenic impact on L. lithophaga habitat (e.g., Fanelli et al 1994;Devescovi et al 2005;Parravicini et al 2010;Guidetti 2011), different aspects of tissue contamination (Dujmov and Sučević 1990;Deudero et al 2007;Jaafar Kefi et al 2012a, b), or reproduction (Valli et al 1986;Šimunović et al, 1990;Sinis 1994, 1997;Jaafar Kefi et al 2014). Lithophaga lithophaga reproduces once a year following a decline in sea water temperature and has an unequal sex ratio, with males being dominant at smaller size categories (Galinou-Mitsoudi and Sinis 1994; Jaafar Kefi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results showed that the b value of length-height and length-width relationships was 0.2877 and 0.2783 for the annual population. In Bizerte Bay (Tunisia), Kefi et al (2014) reported b values of 1.1148 for length-height and 0.9918 for length-width relationships for L. lithophaga mussel for the annual population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted on this species primarily examined those aspects of L. lithophaga biology related either directly or indirectly to fisheries, because L. lithophaga is regarded as a food source. These include analyses of its population structure and settlement ( Simunovi c and Grubeli c, 1992;Sinis, 1995, 1997a;Devescovi and Ive sa, 2008), reproduction (Valli et al, 1986;Simunovi c et al, 1990;Sinis, 1994, 1997b;Jaafar Kefi et al, 2014) and different aspects of tissue contamination (Dujmov and Su cevi c, 1990;Deudero et al, 2007;Jaafar Kefi et al, 2012a, 2012bOzsuer and Sunlu, 2013). More than 20 years ago, however, Fanelli et al (1994) warned that the recovery of exploited stocks of L. lithophaga may be slow.…”
Section: Introductionmentioning
confidence: 99%